Effects of Exercise and Physical Activity on Happiness of Postmenopausal Female - Mohsen Salesi; Bahram Jowkar (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The aim of this research was to study the effect of exercise on happiness in old women. Methods & Materials: 72 sedentary postmenopausal women participated in this study. Participants were randomized into three exercise group (walking, weight training and water exercise) and one control group. The experimental groups contributed in an 8 week training with given intensity and duration. The control group was asked to continues their usual daily routines during the 8 week experimental period. The instrument of study was Revised version of Oxford Happiness Questionnaire (OHQ-R) that was measured before and after the exercise program. Data were analyzed by one way analysis of variance (P<0.05). Results: The findings revealed significantly differences between groups. The results showed the effect of exercise participation on improving happiness and weight training group had most effect in relation with control group. Conclusion: Our study has shown improvements in the parameters of happiness in all exercise groups. Administration of a regular exercise program will be beneficial to sedentary postmenopausal women. It is considered appropriate that old women can benefit from all kind of exercise that introduce in this study for diminish postmenopausal problems.